Impact of aging experience suit on neuropsychological performance - Medrano-Martínez, Pablo; Carretero, Isabel; Noriega, Cristina; López, Javier; Pérez-Rojo, Gema (Frontiers in Psychology, 2025)
IntroductionAlthough the effect of Aging experience suit (AES) interventions in the increase of empathy and positive attitudes toward older adults has been well studied, the evidence about the influence of the AES in neuropsychological performance remains limited. The aims of this study were to assess the effect of wearing an AES during neuropsychological evaluation and describe how physical and visuoperceptual restrictions could affect the interpretation of the results.MethodsWe studied 48 subjects (72.9% females; mean age, 19.50 ± 0.61 years). All participants completed two testing sessions: one wearing the AES and another without it. They underwent neuropsychological tests for attention and executive function, Trail Making Test (TMT) and Cancellation Task, and completed a dual task. The dual-task conditions included walking and backward counting simultaneously. Heart rate was recorded to measure fatigue.ResultsParticipants demonstrated poorer performance on both, TMT-A and TMT-B while wearing the AES, however no significant differences were observed in the derived TMT indices. In the cancellation task, AES condition participants processed fewer stimuli and achieved less correct responses. In the dual-task assessment, performance while wearing the suit decreased significantly. Participants appeared to prioritize the cognitive component (backward counting) over the motor task (walking), as evidenced by the reduced walking distance, suggesting a shift in attentional focus toward the secondary task.ConclusionThe results of the neuropsychological tests indicated generalized poorer performance in the suit condition. AES leads to an impaired performance on standardized neuropsychological tests.